Monkey-monkey's trick - McKissack, Patricia (New York : Random House, 1988)
A greedy hyena's mean tricks on Monkey-Monkey eventrually backfire when his victim finds out how he is being decieved.
Keywords: Monkeys-Fiction; Hyenas-Fiction